Casein kinase 1 is a therapeutic target in chronic lymphocytic leukemia - Janovska, Pavlina; Verner, Jan; Kohoutek, Jiri; Bryjova, Lenka; Gregorova, Michaela; Dzimkova, Marta; Skabrahova, Hana; Radaszkiewicz, Tomasz; Ovesna, Petra; Vondalova Blanarova, Olga; Nemcova, Tereza; Hoferova, Zuzana; et al. (Blood, 2018)
Casein kinase 1δ/ε (CK1δ/ε) is a key component of noncanonical Wnt signaling pathways, which were shown previously to drive pathogenesis of chronic lymphocytic leukemia (CLL). In this study, we investigated thoroughly the effects of CK1δ/ε inhibition on the primary CLL cells and analyzed the therapeutic potential in vivo using 2 murine model systems based on the Eµ-TCL1-induced leukemia (syngeneic adoptive transfer model and spontaneous disease development), which resembles closely human CLL. We can demonstrate that the CK1δ/ε inhibitor PF-670462 significantly blocks microenvironmental interactions (chemotaxis, invasion and communication with stromal cells) in primary CLL cells in all major subtypes of CLL. In the mouse models, CK1 inhibition slows down accumulation of leukemic cells in the peripheral blood and spleen and prevents onset of anemia. As a consequence, PF-670462 treatment results in a significantly longer overall survival. Importantly, CK1 inhibition has synergistic effects to the B-cell receptor (BCR) inhibitors such as ibrutinib in vitro and significantly improves ibrutinib effects in vivo. Mice treated with a combination of PF-670462 and ibrutinib show the slowest progression of disease and survive significantly longer compared with ibrutinib-only treatment when the therapy is discontinued. In summary, this preclinical testing of CK1δ/ε inhibitor PF-670462 demonstrates that CK1 may serve as a novel therapeutic target in CLL, acting in synergy with BCR inhibitors. Our work provides evidence that targeting CK1 can represent an alternative or addition to the therapeutic strategies based on BCR signaling and antiapoptotic signaling (BCL-2) inhibition.
Keywords: Animals; pyrimidiny; kaseinkinasa Idelta; Cell Line, Tumor; HEK293 Cells; Casein Kinase 1 epsilon; Leukemia, Lymphocytic, Chronic, B-Cell; Pyrazoles; lidé; pyrazoly; Mice; myši; HEK293 buňky; Drug Delivery Systems; nádorové proteiny; Neoplasm Proteins; lékové transportní systémy; zvířata; Casein Kinase Idelta; kaseinkinasa Iepsilon; chronická lymfatická leukemie; nádorové buněčné linie; Pyrimidines; Humans